2014
DOI: 10.1002/lary.24993
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal and ventral skull base Inflammatory pseudotumor: A systematic review

Abstract: Objectives/Hypothesis Inflammatory pseudotumor is a benign idiopathic inflammatory process often misdiagnosed as an infection or neoplasm. This review analyzes all reported cases of sinonasal and ventral skull base inflammatory pseudotumor to date, and provides a framework for evaluation and management of this uncommon condition. Data Sources MEDLINE/PubMed database. Review Methods A search for articles related to sinonasal and ventral skull base inflammatory pseudotumor, along with bibliographies of those art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 27 publications
0
40
0
Order By: Relevance
“…It also occurs in different extrapulmonary locations, such as the abdomen, retroperitoneum, pelvis, heart, head and neck, upper respiratory tract, trunk, bladder, and extremities . The locations of IMT in the head and neck include skull base, nose, paranasal sinus, larynx, hypopharynx, orbit, brain, temporal bone, parapharyngeal space, middle or inner ear, thyroid gland, and carotid artery, among which paranasal sinus is the most common site, followed by the larynx . The meaning of medical imaging technology in the diagnosis of IMT is controversial in some literature, and the infiltrative margin of the lesion is often interpreted as malignancies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also occurs in different extrapulmonary locations, such as the abdomen, retroperitoneum, pelvis, heart, head and neck, upper respiratory tract, trunk, bladder, and extremities . The locations of IMT in the head and neck include skull base, nose, paranasal sinus, larynx, hypopharynx, orbit, brain, temporal bone, parapharyngeal space, middle or inner ear, thyroid gland, and carotid artery, among which paranasal sinus is the most common site, followed by the larynx . The meaning of medical imaging technology in the diagnosis of IMT is controversial in some literature, and the infiltrative margin of the lesion is often interpreted as malignancies .…”
Section: Discussionmentioning
confidence: 99%
“…If there is any recurrence, corticosteroids can be administered again. Radiotherapy is regarded as the most controversial modality that can be used when en bloc resection cannot be achieved and/or corticosteroids do not work . For those patients with immunoglobulin G4–related IMT, corticosteroids may be a good choice, but how long corticosteroids should be taken, life‐long or short‐term, remains a question .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on sinonasal and ventral skull base IPT also found that similar to orbital IPT, corticosteroids treatment alone was the most common (55.2%) therapeutic modality used for these lesions, and resulted in disease‐free patients in 22.9% of the cases . That systematic review also showed that corticosteroids and radiotherapy was the second most common treatment modality for sinonasal and ventral skull base IPT . Surgery alone was the third most common treatment modality for this condition and resulted in high success rate …”
Section: Discussionmentioning
confidence: 89%
“…For a subset of patients with recalcitrant disease and relentless progression, orbital exenteration may be required . A recent systematic review on sinonasal and ventral skull base IPT also found that similar to orbital IPT, corticosteroids treatment alone was the most common (55.2%) therapeutic modality used for these lesions, and resulted in disease‐free patients in 22.9% of the cases . That systematic review also showed that corticosteroids and radiotherapy was the second most common treatment modality for sinonasal and ventral skull base IPT .…”
Section: Discussionmentioning
confidence: 99%
“…Yet consensus on the optimal treatment for IMT is still lacking. In a review of 87 patients with sinonasal and base of skull IMT, Desai et al found surgical resection to be the most successful approach, with corticosteroids also showing significant benefit in disease management 14. Only when radiotherapy was combined with surgery did it seem to show a treatment benefit.…”
Section: Discussionmentioning
confidence: 99%